Validation of Minimally-Invasive Sample Collection Methods for Measurement of Telomere Length - Stout, Stephanie A.; Lin, Jue; Hernandez, Natalie; Davis, Elysia P.; Blackburn, Elizabeth; Carroll, Judith E.; Glynn, Laura M. (Frontiers in Aging Neuroscience, 2017)
Objective: The discovery of telomere length as a biomarker of cellular aging and correlate of age-related disease has generated a new field of research in the biology of healthy aging. Although the most common method of sample collection for telomere length is venous blood draw, less-invasive DNA collection methods are becoming more widely used. However, how telomere length relates across tissues derived from these sample collection methods is poorly understood. The current study is the first to characterize the associations in telomere length across three sample collection methods: venous whole blood, finger prick dried blood spot, and saliva. Methods: Telomere length was measured in 24 healthy young adults using three modes of sample collection for each participant: venous whole blood, finger prick dried blood spot, and saliva. Relative telomere length was measured using quantitative polymerase chain reaction. Results: Telomere length in finger prick DBS was highly correlated with telomere length in whole blood (r=.84, p<.001). Salivary telomere length was also correlated with whole blood telomere length (r = .56, p=.005), but this association was not as strong as that of dried blood spot telomere length (Steiger’s Z = 2.12, p = .034). Telomere length was longer in saliva than in whole blood or DBS (p’s<.001). Conclusions: These findings have important implications for future study design by supporting the validity of less-invasive methods that can be implemented with vulnerable populations or in the field. Further, these findings aid in interpreting the burgeoning area of biological aging research and may shed light on our understanding of inconsistencies in the empirical literature.